1993
DOI: 10.1111/j.2044-8325.1993.tb00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping with job stress: Which strategies work best?

Abstract: In a four‐wave panel study the coping styles of case managers hired to work with seriously and persistently mentally ill clients were measured at entry to the job. Workers' degree of stress, strain and negative consequences, such as burnout, job dissatisfaction, physical symptoms, intention to quit and life dissatisfaction, were assessed at subsequent time periods (three, 12 and/or 18 months later). Depending on time period and outcome variable studied, the effect of coping was examined in between 39 and 51 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
134
2
10

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(156 citation statements)
references
References 7 publications
10
134
2
10
Order By: Relevance
“…Empirical research has shown that active or problem focused coping is linked to increases in job satisfaction and decrease in exhaustion 32,33,35) . Previous studies have shown that direct action strategies reduced the relationship between excessive work demands and job satisfaction, and palliative coping strategies increased the relationship between stressor and depersonalization 34) . Several authors have suggested that coping training programs may be effective in improving the management of stressful events 36−38) .…”
Section: Discussionmentioning
confidence: 94%
“…Empirical research has shown that active or problem focused coping is linked to increases in job satisfaction and decrease in exhaustion 32,33,35) . Previous studies have shown that direct action strategies reduced the relationship between excessive work demands and job satisfaction, and palliative coping strategies increased the relationship between stressor and depersonalization 34) . Several authors have suggested that coping training programs may be effective in improving the management of stressful events 36−38) .…”
Section: Discussionmentioning
confidence: 94%
“…Chan e Hui (1995) corroboram esse achado, em pesquisa com professores chineses, ao demonstrarem uma associação positiva entre o uso de estratégias de evitação e o aumento dos níveis de Burnout. Em estudo longitudinal com trabalhadores sociais, Koeske, Kirk, & Koeske (1993) verificou que a utilização de estratégias focalizadas no problema promove uma melhor capacidade de enfrentar as situações difíceis no trabalho.…”
Section: Prevalencia Y Predictores De Burnout En Bomberosunclassified
“…Coping strategies are related to burnout, in favor of positive strategies like planning, restraint coping and non-denial (Dorz et al, 2003) while negative coping strategies like avoidance, denial or inactive/passive are mainly with low uses (Slagle, 1996;Leiter & Harvie, 1996;Cushway & Tyler, 1994;Koeske, Kirk, & Koeske, 1993;Thorton, 1992). Using of coping strategies is correlated with the level of burnout, also, coping strategies observed to be as a protective factor from burnout among the nurses (GueritaultChalvin et al, 2000).…”
Section: Stressmentioning
confidence: 99%